Microregional Hybridity: On the (Un)Sustainability of the Urban/Rural Dichotomy - Lehečka, Michal (Lidé města, 2017)
In 2016, I was involved in applied research that was focused on the regional conceptualizations and perceptions of the media contents about current migration issues in Europe. During analysis, I realized that the data speak about the specific situations of the villagers and their local strategies and struggle against their feelings of increasing peripherality, marginality, and inferiority. To be precise, instead of migration issues, I became really interested in the socio-economical and infrastructure topics connected to the Loužná Microregion.